Let it be morning [videorecording (DVD)] - Kolirin, Eran, 1973-; Bakri, Alex; Suleiman, Juna; Dau, Salim; Salāmah, Īhāb, 1969-; Natour, Khalifa; Ramadan, Izabel; Bisharat, Samer, 1996-; Liddawi, Doraid, 1984-; Jarrar, Yara; Qashu, Sayed, 1975- (Contemporary classics (Cohen Media Group), 2023)
Sami lives in Jerusalem with his wife and child, and an invitation to his brother's wedding forces him to return to the Arab village where he grew up. After the wedding, with no warning or explanation, the village is put under military lockdown by Israeli soldiers and cut off from the outside world. Chaos rises overnight amongst those stuck within the walls.